Islamic Education and Daâwah Liberalization: Investigating Kiai Achmad Dachlanâs Ideas - Mulkhan, Abdul Munir (Al-Jamiah Research Centre, Sunan Kalijaga State Islamic University, 2008)
This article discusses two opposing views in regard to Islamic teaching; whether it should be seen as a static entity or as a dynamic one and each option has its own implication. Being seen as a static entity, Islamic teachings cannot be put on the table of criticism, because it is supposed to be perfect, correct, and its validity goes beyond time and space. In this position, Islamic teaching that is taught in Islamic education institutions is delivered in non dialogical way, assuming that it is doctrine, not knowledge. The author argues that such view would possibly make Islamic teachings become ânormal scienceâ that loose their relevances to contemporary human life. In fact, what is considered as Islamic teachings cannot be separated from human intervention since parts of them are formulated by classical Muslim scholars. For this reason, it is necessary to liberate Islamic teachings from narrow-minded perspective and interpretation, as suggested by the proponents of Liberal Islam. Islam should be interpreted in open-mind perspective so that it is possible to bear many different interpretations based on interpretersâ social and academic backgrounds. Achmad Dachlan is one of Muslim scholars who tried to take the essence of Islamic teachings. He argued that one of the main purposes and substantial point of Islamic teachings are the ethical kindness and human happiness. Dachlanâs concern with the marginalized and disfranchised people is based on his view on human ethics and it serves as the foundation of a movement to empower marginalized people.